Le mot et l’orage. La poésie concrète de Pierre Garnier - Sara Svolacchia (Lea, 2020)
This article aims at describing Pierre Garnier’s itinerary from traditional, linear poetry, to concrete, visual poetry. Born as a reaction to the mainstream political-oriented poetry campaigned by Aragon, French concrete poetry is characterised by the use of language as “matter”, namely by the aim to destroy the linear syntax of discursive communication. Thus, poetry can become fully “universal”, no longer needing any form of translation. Garnier experiments during the Sixties and the Seventies include juxtapositions of letters (Poèmes mécaniques) and the combination of ideograms and Latin alphabet (Poèmes franco-japonais). The radicalisation of these attempts is a form of poetry which is very close to silence, almost devoid of linguistic signs and thus very close to pictorial art.